Eventually periodic solutions of single neuron model - Bula, Inese; Radin, Michael A. (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we consider a nonautonomous piecewise linear difference equation that describes a discrete version of a single neuron model with a periodic (period two and period three) internal decay rate. We investigated the periodic behavior of solutions relative to the periodic internal decay rate in our previous papers. Our goal is to prove that this model contains a large quantity of initial conditions that generate eventually periodic solutions. We will show that only periodic solutions and eventually periodic solutions exist in several cases.
Keywords: neuron model; difference equation; periodic solution; eventually periodic solution